CURRICULUM MANAGEMENT OF IDAD MURABBI PROGRAM IN IMPROVING THE QUALITY OF PROSPECTIVE EDUCATORS: A CASE STUDY AT STIPI MAGHFIRAH - El Hanif, Zubair Qudsi; Sastra, Ahmad; Sa'diyah, Maemunah; Azhar, Rayhan; M. Nur, Firman (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Teacher quality is factor key quality Islamic education is required balance competence academic and character . Research This analyze management I'dad Murabbi Program curriculum at STIPI Maghfirah , cadre development model intensive